2021
DOI: 10.1002/anie.202111853
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin D Inhibits the Early Aggregation of α‐Synuclein and Modulates Exocytosis Revealed by Electrochemical Measurements

Abstract: Alpha‐synuclein (α‐Syn) localizes at presynaptic terminal and modulates synaptic functions. Increasing evidence demonstrate that α‐Syn oligomers, forming at the early of aggregation, are cytotoxic and is thus related to brain neurodegenerative diseases. Herein, we find that vitamin D (VD) can reduce neurocytotoxicity. The reduced neurocytotoxicity might be attributed to the less amount of large‐sized α‐Syn oligomers inhibited by VD, measured by electrochemical collision at single particle level, which are not … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(9 citation statements)
references
References 50 publications
0
9
0
Order By: Relevance
“…The specific pathogenesis of PD is not clear yet but it is widely recognized that α-synuclein (α-Syn) protein is the core of pathogenesis of the disease [ 95 ]. α-Syn aggregation is cytotoxic, causing cellular damage and dysfunction [ 96 , 97 ].…”
Section: Effects and Molecular Mechanisms Of Vitamin D In Neurodegene...mentioning
confidence: 99%
See 2 more Smart Citations
“…The specific pathogenesis of PD is not clear yet but it is widely recognized that α-synuclein (α-Syn) protein is the core of pathogenesis of the disease [ 95 ]. α-Syn aggregation is cytotoxic, causing cellular damage and dysfunction [ 96 , 97 ].…”
Section: Effects and Molecular Mechanisms Of Vitamin D In Neurodegene...mentioning
confidence: 99%
“…Vitamin D also could reduce the cytotoxicity caused by α-synuclein aggregation in the early state by down-regulating the production of ROS. Cell death and apoptosis might result from the inhibition of α-Syn aggregation for strong affinity energy to α-Syn monomer [ 96 ]. What’s more, vitamin D could also decrease the exocytotic release of neurotransmitters raised by α-Syn oligomers, indicating the neuroprotective effect of vitamin D in PD [ 96 ].…”
Section: Effects and Molecular Mechanisms Of Vitamin D In Neurodegene...mentioning
confidence: 99%
See 1 more Smart Citation
“…Reduced levels of voltage dependent anion channel protein 1 (VDAC1) in the SNpc neurons of sporadic PD patients was associated with aggregations of α-syn ( Chu et al, 2014 ), which may have been mediated by the activation of the mitochondrial permeability transition pore (mPTP). Aggregated α-syn affects various cellular functions, including mitochondrial function, autophagy, protein transcription, and synaptic function ( Tang et al, 2021 ; Zhang et al, 2022 ). Transcriptomic analysis of induced pluripotent stem cells (iPSCs) carrying an A53T SNCA mutation and a triplication discovered that the expression of mitochondrial function-related genes was perturbed ( Zambon et al, 2019 ), which could explain the observed reduction in mitochondrial respiration, aberrant mitochondrial morphology, and decreased mitochondrial membrane potential.…”
Section: Genes Associated With Mitochondrial Dysfunction In Parkinson...mentioning
confidence: 99%
“…19 Zhang and co-workers monitored the formation process of α-synuclein oligomers within 3 days by comparing the current intensity in the absence and presence vitamin D (VD) and found the neuroprotective role of VD through inhibiting α-synuclein aggregation. 31 Overall, the conventional SNEC measures single-impact events of an agglomeration/aggregation colliding on a base microelectrode and monitors current intensity or charge passed per spike at a fixed potential value, which can be related to the size of the agglomeration/aggregation. Considering that the experimental current intensity or charge is always different from the theoretical value owing to the effect of NPs movements on electrode surfaces, the conventional SNEC is limited in the accurate analysis of NPs agglomeration/aggregation.…”
mentioning
confidence: 99%